Two new Hypomyces associated with boletoid fungi in China - Gu, Xin; Fu, Rong; Wang, Rui; Sun, Jing-Zu (Phytotaxa, 2021)
During an investigation of fungicolous fungi associated with mushrooms in China, four boleticolous fungi were collected from Sichuan Province. Based on the morphological features and multi-gene phylogenetic analyses this study introduces two new species, Hypomyces ampullaris, and H. sichuanensis. The new species are described and illustrated comprehensively and compared with their related fungi. Hypomyces ampullaris is similar to Sepedonium ampullosporum in forming candelabrum-like conidiophores and producing ampulliform conidia but differs from the latter in having shorter phialides and smaller ampulloconidia. Hypomyces sichuanensis is similar to H. chrysospermus, H. microspermus, and Sepedonium laevigatum in forming poorly developed verticills conidiophores and the shape and size of aleurioconidia. However, the asexual spores of H. sichuanensis averaged somewhat smaller than those of H. chrysospermus and S. laevigatum, and larger than that of H. microspermus. Additionally, H. ampullaris and H. sichuanensis distinct from their close relatives in no pigment discoloration of the PDA medium. These species introduced here, improve our understanding of the diversity of Hypomyces, especially of the boleticolous Hypomyces in China.